Elevated water temperature increases the levels of reo-like virus and selected innate immunity genes in hemocytes and hepatopancreas of adult female blue crab, Callinectes sapidus. Issue 1 (November 2015) - Chung, J. Sook; Pitula, J.S.; Schott, E.; Alvarez, J.V.; Maurer, L.; Lycett, K.A.
Abstract: Seasonal changes in water temperature directly affect the aquatic ecosystem. The blue crab, Callinectes sapidus, inhabiting the Chesapeake Bay has been adapted to seasonal changes of the environmental conditions. In this, the animals halt their physiological process of the growth and reproduction during colder months while they resume these processes as water temperatures increase. We aimed to understand the effect of the elevated temperatures on a disease progression of reo-like virus (CsRLV) and innate immunity of adult female C. sapidus . Following a rise in water temperature from 10 to 23 °C, CsRLV levels in infected crabs rose significantly in hemocytes and multiple organs. However, in hemocytes, the elevated temperature had no effect on the levels of three innate immune genes: Cas-ecCuZnSOD-2, CasPPO and CasLp R three carbohydrate metabolic genes: CasTPS, CasGlyP ; and CasTreh and the total hemocyte counts (THC). Interestingly, the hemocytes of CsRLV infected animals exposed to 23 °C for 10 days had significantly elevated levels of Cas-ecCuZnSOD-2 and CasTPS, compared to those of the uninfected ones also exposed to the same condition and compared to hatchery-raised females kept at 23 °C. Despite the lack of changes in THC, the types of hemocytes from the animals with high CsRLV levels differed from those of uninfected ones and from hatchery animals kept at 23 °C: CsRLV-infected crabs had hemocytes of smaller size with less cytosolic complexity than uninfected crabs. It therefore appears that the change in temperature influences rapid replication of CsRLV in all internal tissues examined. This implies that CsRLV may have broad tissue tropism. Interestingly, the digestive tract (mid- and hindgut) contains significantly higher levels of CsRLV than hemocytes while hepatopancreas and ovary have lower levels than hemocytes. Innate immune responses differ by tissue: midgut and hepatopancreas with upregulated Cas-ecCuZnSOD-2 similar to that found in hemocytes. By contrast, hepatopancreas showed a down-regulated CasTPS, suggesting carbohydrate stress during infection. Highlights: Elevated temperature increases the levels of RLV in hemocytes. Hemocytes of RLV-infected females have significantly high levels of Cas-ecCuZnSOD-2 expression. Hemocytes and hepatopancreas of RLV-infected females also contain significantly high levels of CasTPS expression. Hepatopancreas and hindgut of RLV-infected animals show significantly low levels of Cas-ecCuZnSOD-2 expression. RLV-infected animals contain high portions of small sized hemocytes.